Literature study in higher education: learning from an implementation process: Knowledge from a process of change - folkman, anne katrine; Haga, Britt Marit; Areskoug Josefsson, Kristina (Nordisk Tidsskrift for Helseforskning, 2022)
This article describes learning from an educational development project in higher education. The project included changing to performing literature reviews in bachelor theses bachelor programs spring 2021. The objective of this article is to present pedagogical and didactical experiences, and knowledge production in the change process, relevant for other programs. Focus of the development project was both students´ and teachers´ learning, to promote better quality of education and lifelong learning for professional practice.
Keywords: GDPR; literature review; higher education; pedagogic development